Teaching Writing Skills through Descriptive Text by Using Digital Storytelling “StoryJumper” - Rahma Fitriyani; Muhamad Ahsanu; Mustasyfa Thabib Kariadi; Slamet Riyadi (Universitas Pekalongan, 2023)
The aims of this study are to describe the implementation of StoryJumper, to describe the students’ skills in writing descriptive text after being taught using StoryJumper, and to explain the teacher’s and student’s perceptions toward the use of StoryJumper at the tenth-grade of MA Al Ikhsan Beji in the Academic Year 2022/2023. This study used Classroom Action Research (CAR). The subjects of this research were students in class X Social Science 1. The data were collected from observations, tests, and interviews. The result of this research shows that teaching writing skills through descriptive text using digital storytelling “StoryJumper” run effectively. It could be seen from the result of the observation that the teacher and the students could implement StoryJumper as a medium for teaching writing descriptive text properly. The students’ skills in writing descriptive text improved after the implementation of StoryJumper. From the result of the tests, the mean scores increased from 48.95 in pre-test to 71.94 in post-test 1 and to 80.38 in post-test 2. The students’ scores were analyzed using the Paired Samples T-Test in SPSS 20. The result shows that the p-value is 0.000 which is less than 0.05. It means that the result is statistically significant. The teacher and students also had positive perceptions toward the use of StoryJumper. Furthermore, it can be concluded that digital storytelling “StoryJumper” is effective to be used as a learning medium for writing descriptive text. Keywords: Teaching Writing, Descriptive Text, Digital Storytelling StoryJumper